Maximum-A-Posteriori Signal Recovery with Prior Information: Applications to Compressive Sensing - Bereyhi, Ali; Müller, Ralf (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2018)
This paper studies the asymptotic performance of maximum-a-posteriori estimation in the presence of prior information. The problem arises in several applications such as recovery of signals with non-uniform sparsity pattern from underdetermined measurements. With prior information, the maximum-a-posteriori estimator might have asymmetric penalty. We consider a generic form of this estimator and study its performance via the replica method. Our analyses demonstrate an asymmetric form of the decoupling property in the large-system limit. Employing our results, we further investigate the performance of weighted zero-norm minimization for recovery of a non-uniform sparse signal. Our investigations illustrate that for a given distortion, the minimum number of required measurements can be significantly reduced by choosing weighting coefficients optimally.
Keywords: Maximum-a-posteriori estimation; Compressive sensing; Weighted norm minimization; Decoupling property; Replica method